The Impact of Being Present During Resuscitation on Family Members: A Scoping Review Protocol - Ira Rahmawati; Tamara Page; Lisa Conlon; Frank Donnelly (Health Science Reports)
ABSTRACT Background and Aims Family members of patients who are undergoing resuscitation may experience complex psychological challenges, including anxiety, depression, or posttraumatic stress symptoms. Although several studies have identified positive experiences of family members who were given the option to be present during their loved one's resuscitation, the actual impact of family presence during resuscitation on family members remains elusive and needs to be explored comprehensively. This review aims to identify the impact of being present during the resuscitation event of adult patients in in‐hospital settings on family members. Methods The proposed review will utilize the JBI methodology for scoping reviews. This review will include literature from all study designs that are published in English with no date restrictions. The inclusion criteria include studies evaluating the impact on family members after witnessing the resuscitation of a loved one or being present at the hospital during the event. This review will include studies conducted in intrahospital settings, including emergency departments, critical care units, and in‐hospital wards. This study will also emphasize the influences of social, cultural, and spiritual factors on FPDR practices. A systematic search will be conducted across five databases and gray literature. These include PubMed, CINAHL (EBSCO), Embase, Emcare, and PsycINFO, ProQuest Database, Open Access Theses and Dissertations, and Google Scholar. Two independent reviewers will screen titles and abstracts and assess the full text of selected articles against inclusion criteria. Discussion with all reviewer team members will be held when disagreements arise between the reviewers at each review stage. Data will be analysed and presented according to The Preferred Reporting Items for Systematic reviews and Meta‐Analyses extension for Scoping Review. Scoping Review Registration This scoping review protocol was registered with Open Science Framework (https://doi.org/10.17605/OSF.IO/U6AW8).